Dübörög a nemzeti rock - Kriza, Bori (Hungary : Metaforum Film, 2007)
A concert tour with ”Romantic Violence”, the cult band of ”national rock”, and its fans from December 2005 till the fall of 2006. Folk musicians and skinheads, football fans and college students speak of their radical nationalistic views. They started out as a high school band in the 90’s, but today they are one of the top representatives of “national rock”. They claim they are patriots; their role models are the freedom fighters of ’56. They tour former Hungarian territories annexed by Romania and Serbia, play in clubs and at the Hungarian Sziget Festival. They travel tirelessly, for their music is their mission, “to strengthen national identity”, “to shake people up”, “to make people think” at home and abroad. Their concerts are much more than a party for the fans: they have created a community, and a way of life. They sing folk-rock numbers, legends and revisionist songs along with the Ferencvaros football team anthem. Their slogans are rocking: freedom, anti-Communism, Trianon, the Jews, Hungary, to arms!
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films